2006
DOI: 10.5387/fms.52.79
|View full text |Cite
|
Sign up to set email alerts
|

Possible Association of Cytotoxic T Lymphocyte Antigen-4 Genetic Polymorphism With Liver Damage of Primary Biliary Cirrhosis in Japan

Abstract: Cytotoxic T lymphocyte antigen-4 (CTLA-4) is an important inhibitor of T -lymphocyte response. Polymorphisms in the CTLA-4 gene have been reported to be associated with numerous autoimmune diseases. The aim of this study was to determine whether polymorphisms of CTLA-4 exon 1 (+49) genes are associated with susceptibility and clinicolaboratory findings of primary biliary cirrhosis (PBC) in the J apanease population. Blood samples were obtained from 45 patients (6 men and 39 women, aged 23-56 years) with PBC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
(3 reference statements)
2
14
0
Order By: Relevance
“…Our finding corroborated a previous report [31], in which 49AG was not associated with susceptibility to PBC but there was a discrepancy in association with liver damage that might have arisen from the number of cases analyzed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our finding corroborated a previous report [31], in which 49AG was not associated with susceptibility to PBC but there was a discrepancy in association with liver damage that might have arisen from the number of cases analyzed.…”
Section: Discussionsupporting
confidence: 83%
“…Although early studies found an association between SNP 49G coding and PBC [22][23][24], ensuing reports showed negative relationships with susceptibility [25][26][27][28][29][30] or a positive association with liver damage [31]. A recent investigation reported that rs231725 in the 3'…”
Section: Introductionmentioning
confidence: 99%
“…The association between CTLA4 SNPs and liver damage has been studied in two papers. Kanno et al [17] identified that the CTLA4 +49 (rs231775) genotype was positively associated with liver damage in primary biliary cirrhosis (PBC) in Japanese populations and that PBC patients with the G/G genotype had significantly higher serum levels of ALT, GGT, and IgM than did patients with the A/A or A/G genotype. Valenti et al [18] observed a significantly higher prevalence of the susceptible CTLA4 allele (both in the heterozygous [OR 2.5] and in the homozygous [OR 4.6] state) in patients with alcoholic liver disease (ALD) compared to healthy subjects; this relationship was independent of age, sex and geographical origin.…”
Section: Discussionmentioning
confidence: 99%
“…Kanno et al [17] discovered that SNP CTLA4 +49GG (rs231775) may be associated with the liver damage of primary biliary cirrhosis (PBC) in Japanese populations. Valenti et al [18] observed a significantly higher prevalence of subjects carrying the CTLA4 susceptibility allele (both in the heterozygous and homozygous states) among patients with ALD compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Additional regions within the major histocompatibility complex have also been linked with PBC and the combination of the complement component C4 null allele and DRB1 Ã 08 provides a 180-fold increased relative risk for disease (6). Other genetic correlations with PBC patients include the vitamin D receptor (8)(9)(10)(11), cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) (12)(13)(14)(15)(16), natural resistance-associated macrophage protein 1 (17), tumour necrosis factor-a promoter (18), the mannosebinding lectin gene (19) and interleuklin-1 gene (5). Apart from DRB1 Ã 08, these associations have not been consistently confirmed although CTLA-4 may be associated with PBC in specific populations (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%